2018
DOI: 10.4055/cios.2018.10.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Is Immediate Postoperative Mechanical Axis Associated with the Revision Rate of Primary Total Knee Arthroplasty? A 10-Year Follow-up Study

Abstract: BackgroundAchieving neutral limb alignment during total knee arthroplasty (TKA) has been considered an important determinant in the long-term prosthesis survival. The purpose of this study was to evaluate the association between the immediate postoperative mechanical alignment of the lower limb and the rate of revision TKA by comparing an acceptable mechanical axis group (within ± 3° from neutral alignment) and an outlier group (> 3° deviation from neutral alignment).MethodsBetween 2000 and 2006, clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Malalignment of the knee produces pathologic stress on the unicompartmental joint space of the knee, increasing the risk of accelerated degenerative changes [ 2 ]. The current recommendation addresses lower limb angular deformities using mechanical axis assessment as early as possible to prevent consequences such as altered gait patterns, early articular cartilage degeneration, and soft tissue changes [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malalignment of the knee produces pathologic stress on the unicompartmental joint space of the knee, increasing the risk of accelerated degenerative changes [ 2 ]. The current recommendation addresses lower limb angular deformities using mechanical axis assessment as early as possible to prevent consequences such as altered gait patterns, early articular cartilage degeneration, and soft tissue changes [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 12 This has been supported by studies which have shown lower revision rates in patients in whom the coronal alignment of the component was within 3° of neutral. 14 , 15 However, this concept overlooks the variable natural alignment seen by Bellemans et al 6 in the pre-disease knee of adolescents and young adults. Implanting components perpendicular to the mechanical axis may be beneficial for implant survivorship, but risks altering the patient's bony anatomy and may require more aggressive capsular and ligament releases to obtain soft tissue balancing.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Although some studies have suggested that postoperative coronal lower limb and knee alignment (HKAA, MDFA, and MPTA) outside 3° from neutral does not predict implant failure, 26 28 most existing literature advocates keeping within this ‘safe zone’. 12 15 , 29 The effectiveness of kinematically aligned TKA may therefore be limited for patients with constitutional varus or valgus beyond 3° from neutral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TKA is currently being performed to a relatively younger population, 9 and obtaining the coronal alignment of 0 + 3 is important for implant survival. 10,11 On such basis, the technique of computer-assisted navigation has been integrated to TKA and have been reported to be effective in obtaining the coronal alignment of 0 + 3 . [12][13][14] However, the fact that obtaining coronal alignment of 0 + 3 in all types of cases, regardless of cases with severe varus deformity, is questionable.…”
Section: Discussionmentioning
confidence: 99%